(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Layer-by-layer detailing processes, which used wire and electric arc - wire arc additive manufacturing (WAAM), are among the most productive in 3D metal printing technologies. From this point of view, the solution of the thermal task, and subsequently of the deformation problem, are particularly relevant. It is natural that these simulation modelling processes are closely related to welding, but at the same time it is necessary to take into account particularities that are crucial for WAAM and are not always relevant in welding. In this research, one such model is proposed, which takes into account the gradual filling of the working space with the deposited metal. The specific issues related to the construction of the model, the definition of the heat source and the first layer formation in the conditions of WAAM are considered. The obtained numerical results enable the prediction of the layer dimensions.